Institutional Repository Initiatives in Tanzania: Opportunities and Challenges - Muneja, Paul S; Ndenje-Sichalwe, Esther (University of Dar es Salaam Library Journal, 2017)
The changing model of scholarly communication on knowledge sharing and dissemination has brought a new demand for creation of digital repositories to facilitate collection, preservation and archival of scholarly assets created by academics within academic and research institutions. This study investigated the perceptions of the Tanzania academic communities on establishing Institutional Repositories (IR), It also assessed the ICT basic infrastructures and technical capabilities for hosting IR in 10 higher learning institutions in the country. Furthermore, the study assessed the opportunities and challenges for establishing IR. The findings revealed that there is varying perceptions among academics on establishing IR. The findings further revealed that most institutions, although had adequate ICT infrastructure, they had slow Internet connectivity. The study noted lack of technical expertise on managing Free and Open Source Software (FOSS). It also revealed that the majority had limited knowledge about the Open Access. The findings revealed a number of challenges including, low bandwidth, unstable power supply, lack of awareness on IR, lack of knowledge on Intellectual Property Right (IPR), lack of repository policy and lack of funds to run repositories. Furthermore, results show a number of opportunities such as: government ' s efforts to create enabling environments to improve Internet connectivity and growing number of institutions establishing repositories. This study therefore recommends increased advocacy on creation of local content repositories, creation of awareness to academics, researchers, students and institutional top leaders. Collaboration between IR managers and IT personnel in managing IR should also be encouraged.